Personality theory: New factors to incorporate in public decision‐making in communities - Mengyao Yan; Jinzi Zhang; Pu Ge; Yibo Wu (Wiley, 2023)
Abstract Background This study explored the effects of personality factors on public behavioral decision‐making. Methods We examined the literature on personality theory based on triadic interaction decision theory, and summarized and compared the findings with studies of the Big Five personality characteristics. A literature review method was used to explore the implications of personality theory for public decision‐making in Chinese communities. Results Individuals with high neuroticism can be targeted by influential communicators. Individuals with high extraversion can influence decision‐making through interpersonal relationships. Individuals with high levels of openness can be influenced by the development of novel activities. Conscientious individuals respond to scientific and rational knowledge. Individuals with high agreeableness can be influenced by groups. Conclusions Personality traits can influence behavioral decisions and can have positive or negative effects on behavioral outcomes. For people with different personality traits, social actors and social activity communicators should formulate targeted measures according to the classification of personality traits. The current findings have implications for enriching research perspectives and approaches to public community decision‐making.